'How could management let this happen?' Gender, unpaid work and industrial relations in the nonprofit social services sector. (May 2020) - Baines, Donna; Cunningham, Ian
In order to compete in increasingly tight quasi-markets generated by government cutbacks and contracting-out, management in nonprofit agencies have argued that wages and benefits must be reduced or jobs and services will be cut. These arguments have motivated some of the female-majority workers to join and/or organize unions and undertake strike action. Focusing on two case studies exploring restructuring in the highly gendered nonprofit social services in two liberal welfare states (Scotland and Canada), this article explores shifts in industrial relations at the agency level, as well as workforce resistance and union activism. Through the analysis of gendered unpaid work and gendered forms of social and union solidarity, this article extends feminist political economy and mobilization theory. It also suggests convergences at several layers of practice and policy, including private and nonprofit industrial relations cultures, managerialism and the underfunding of contracted-out government services.